Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1016/j.jconrel.2021.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Recent trends of NFκB decoy oligodeoxynucleotide-based nanotherapeutics in lung diseases

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 160 publications
(183 reference statements)
0
11
0
Order By: Relevance
“…Decoy ODNs harboring the consensus DNA recognition motif of a target transcription factor compete with the binding sites in the promoter regions of target genes for the binding of that transcription factor, thereby also significantly reducing the expression levels of downstream genes. Several studies have investigated the application of NF-κB decoy ODNs in the treatment of inflammatory disorders 18 , 19 , highlighting the feasibility of employing RBP-J decoy ODNs for the treatment of diseases resulting from the aberrant activation of Notch signaling.…”
Section: Introductionmentioning
confidence: 99%
“…Decoy ODNs harboring the consensus DNA recognition motif of a target transcription factor compete with the binding sites in the promoter regions of target genes for the binding of that transcription factor, thereby also significantly reducing the expression levels of downstream genes. Several studies have investigated the application of NF-κB decoy ODNs in the treatment of inflammatory disorders 18 , 19 , highlighting the feasibility of employing RBP-J decoy ODNs for the treatment of diseases resulting from the aberrant activation of Notch signaling.…”
Section: Introductionmentioning
confidence: 99%
“…However, one of the major limitations of this approach is the rapid degradation of phosphodiester ODN by intracellular nucleases, which further emphasizes the importance of PLGA as a vector (Ahn et al 2002; Park et al 2003). Previous studies concluded that PLGA NSs were a promising delivery system for a double-stranded decoy ODN to NF-κB (Tahara et al 2011; Mehta et al 2021). Such a system allows sustained ODN release together with an inhibition of the transcriptional activity of NF-κB in activated macrophages at significantly lower concentrations compared with naked ODN (De Rosa et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Another issue of using the modern anti-asthmatic drugs is limited to their efficacy as they are effective only if administered particularly at the time when maintaining the chronotherapy, as the onset of symptoms and exacerbation varies between the patients (Paudel et al 2021). Therefore, a better understanding of the mechanistic pathways (Mehta et al 2020a, b) and investigating alternate novel mechanisms involved in the pathogenesis of asthma are highly needed to develop alternate therapies and new methods of advance drug delivery (example: liquid crystalline nanoparticles, decoy oligonucleotide, extracellular vesicles, and polysaccharides) with minimal side effects and enhanced efficacy (Chan et al 2021a;Manandhar et al 2022;Mehta et al 2021b;Prasher et al 2021).…”
Section: Introductionmentioning
confidence: 99%